Kajian Peningkatan Fungsi Kawasan Perdagangan dan Jasa Regional Didukung Kawasan Permukiman Berkarakter Lokal di Kawasan Konservasi Pasar Besar Kota Malang - Syahyudes Rina (JOURNAL OF APPLIED SCIENCE (JAPPS), 2023)
Pasar Besar district, Klojen sub district, Malang City, East Java is located in the center of Malang City. According on RTRW of Malang City in 2020-2030, Pasar Besar district in the center of Malang City. Klojen is the central Malang City area, where around alun-alun area is city service center located. The activities and functions of the Pasar Besar district are comercial, open space (Tugu Square), housing, forest and sports facilities. The dynamics of existing conditions at Pasar Besar district causes conflicts related to the policy direction of the city system, the basis of city services and the function of strategic economic areas. In one condition it is expected that there will be the development of the Pasar Besar district, but in the other condition concerns about the declining condition of buildings and the growing environment are related to the increase in various activities investment at the Pasar Besar district which comulatively increases the problem of changing the function of the district. The purpose of this study is to examine the improvement of the function of comercial areas supported by residential areas with local characteristics in the conservation area of Pasar Besar Malang City. The data collection method is a mixture of qualitative and quantitative methods using primary and secondary survey techniques. The analysis method uses the analysis method of designing functional areas with an approach to designing the physical elements of urban areas and a sustainable city development approach. Revers to the direction of spatial policy, policy directions related to strategic economic zones, development of the social population, economic growth prospects, physical and environmental analysis related to the function of service centers and the function of regional activities can be known the dynamic model of Pasar Bear district: 1) increasing trade and service investment which will comulatively increase the need for houses and business space and increase the conversion of residential land to comercial, and increase the maximum intensity of comercial land; 2) a decrease in the intensity of maximum residential land, a decrease in the level of quality of the housing environment and comercial. Thus, it is necessary to increase the role of trade and services supported by settlements with local characteristics in the Pasar Besar district through building and environmental planning programs and land conservation efforts